Relasi Agama dan Pertumbuhan Ekonomi: Studi Religiulitas dan Modal Sosial - -, Aprilliantoni (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
This research will prove that: the better the religiosity, the higher the work ethic. This research also wants to show that there is a causal relationship between religion and economic growth. The similarity with academic communities such as Max Weber is that there is a clear causal relationship between religion and economics. Then Adam Smith's view that individual behavior in relation to religion combined together could explain how religion and economics work together. And religious beliefs especially beliefs in heaven, hell and life after death tend to increase economic growth. Meanwhile, Islam itself is closely related to economic growth, which makes it easier for muamalah activities, such as buying and selling and trading. More than that, there is a difference with other academic communities that religion is opium or poison for society. And third parties think that religion is an exogenous factor and that there is no causal relationship between religion and economic growth.